Social representations of lingerie: a study with students and instructors/employees of SENAI Espaço da Moda and with entrepreneurs from the Nova Friburgo/RJ sector (ModaPalavra e-periódico, 2024)
Social representations of lingerie: a study with students and instructors/employees of SENAI Espaço da Moda and with entrepreneurs from the sector of Nova Friburgo Due to the constant presence of the theme in this social environment, it was considered relevant to understand the construction of meanings about “lingerie” by different groups in the city, based on the Theory of Social Representations, developed by Serge Moscovici. In this context, the objective of the study is to investigate social representations of lingerie by students and instructors/employees of SENAI Espaço da Moda and by entrepreneurs in Nova Friburgo/RJ. 10 semi-structured interviews were carried out with each group, analyzed with the support of thematic content analysis. For students, lingerie is “work”, essential for survival; for instructors/collaborators it is “freedom”; and for businessmen it is the “DNA” of the city, which provides solidity for companies. The research revealed that lingerie can be understood through its representations, expressed in sociocognitive processes of groups that reflect their history and social context.
Keywords: social representations; fashion; lingerie